ANALISIS TINGKAT EFISIENSI PENGGUNAAN MODAL MELALUI PENDEKATAN DU PONT SYSTEM PADA PT SIANTAR TOP TBK - Fera Maulina (STIE 'INDONESIA' Pontianak, 2021)
This study aims to describe and analyze the efficiency of the use of capital through the Du Pont approach. The data analysis that will be used is quantitative with the data source, namely secondary data obtained from the 2016-2019 financial statements of PT Siantar Top Tbk. The research variables used are: (1) Asset Turn Over, to show the company's ability to manage all assets to generate sales; (2) Net Profit Margin, to show how much net profit the company gets; (3) Return on Assets, to measure the rate of return of all existing assets; (4) Equity Multiplier, to describe how much equity is compared to the company's total assets or how much assets are financed by debt and; (5) Return on Equity, to measure the rate of return of all existing capital. The results showed that the company's ability to manage its capital in generating net profit was efficient. Factors that affect Return on Equity is the tendency of increasing Net Profit Margin, Total Assets Turn Over, and Return on Assets. This shows that the company's ability to generate net profit from sales, manage assets and investments owned in generating sales and net profit is efficient